THE EFFECTS OF TARGET SETTING ON TARGET COMMITMENT WITHIN THE DGT’S EMPLOYEES OF INDONESIA - Andri - Marfiana (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2017)
AbstractThe purpose of this study is to investigate the level of target commitment in the DGT and the role of target setting theory in effecting this. This research uses Kwan et al. (2013) goal-setting questionnaire. The sample comes from 165 employees of the Directorate General of Taxes (DGT), Indonesia. The result demonstrates that the level of target commitment within the DGT’s employees is high. The effect of target setting factors shows that target clarity and the positive target setting processes positively related with target commitment, whereas target stress, target conflict, and dysfunctional effects of targets negatively related with target commitment. However, high level of target difficulty does not significantly relate to target commitment, strong possibility for moderator. In this study, it is argued that to have a high level of target commitment within the DGT’s employees , It should have a target setting factors to effect this.  Keywords: Target setting, Target Commitment, Public sector, the Directorate General of Taxes, Indonesia.